Nutritional Screening in Cardiac Surgery - V. V. Lomivorotov (Obŝaâ Reanimatologiâ, 2013)
Objective: to compare the informative value of four nutritional screening scales in patients operated on the heart under extracorporeal circulation (EC). Subjects and methods. A prospective cohort study was conducted to examine the results of treatment in 894 adult patients operated on under EC. Nutritional screening was carried out using four scales: Nutritional Risk Screening 2002 (NRS-2002), Malnutrition Universal Screening Tool (MUST), Mini Nutritional Assessment (MNA), and Short Nutritional Assessment Questionnaire (SNAQ). Their nutritional status was assessed by the Subjective Global Assessment (SGA) scale. Mortality and postoperative complications were analyzed. Results. The MUST scale had the highest sensitivity (97.9%) in identifying malnutrition (MN). Univariate analysis of postoperative complications indicated that all the scales had a similar prognostic value: MUST [OR 2 (95% CI, 1.4—2.8); р = 0.0001], SNAQ [OR 1.8 (1.2—2.5); р=0.002], NRS-2002 [OR 1.8 (1.1—3.1); р=0.03], MNA [OR 1.8 (1.3—2.4); р=0.0007] and lower sensitivity (21.2, 23.3, 8.5, and 25.7% for SNAQ, MUST, NRS-2002, and MNA, respectively). However, multivariate analysis along with the commonly known risk factors (age, gender, EC duration) confirmed the prognostic value of the MUST [OR 1.6 (1.1—2.4); р=0.01] and MNA [OR 1.5 (1.1—2.1); р=0.02] scales. Conclusion. The MUST scale is of the most informative value in terms of its sensitivity in detecting MN and of independent prognostic value as to postoperative complications. All the scales have a poor prognostic value regarding the postoperative complications, which determines the urgency of developing a special cardiac screening scale for the nutritional status. Key words: cardiac surgery, nutritional screening, nutritional assessment, malnutrition.